Journal submission challenges: mentoring and training students in open journal system scientific paper publication - Haanurat, A. Ifayani; Darmayanti, Rani; Choirudin, Choirudin (CV. BImbingan Belajar Assyfa, 2024)
Converting student theses or final projects into publishable articles poses a significant challenge. Many students struggle to articulate their ideas in scientific publications due to a lack of writing training. This study aims to identify and address the difficulties students face when submitting papers to scientific journals, particularly using the open journal system. The mentoring and training service implemented comprises four phases: preparation, implementation, analysis, and evaluation. Results indicate that students face challenges in areas such as metadata composition and article submission. However, the training increased student motivation and enthusiasm, enhancing their ability to complete academic assignments and submit them to scholarly journals. This study highlights the necessity of ongoing writing practice and focused mentoring to improve student competencies in scientific paper publication.